Cooperative interception strategy for multiple inferior missiles against one highly maneuvering target - Su, Wenshan; Shin, Hyo-Sang; Chen, Lei; Tsourdos, Antonios (Elsevier, 2018)
This paper proposes a novel cooperative guidance strategy, which aims to intercept one highly maneuvering target with multiple inferior missiles. In the scenario of interest, both the missiles and target are assumed to have bounded maneuverability, and the guidance goal is to make the joint reachable set of interceptors cooperatively cover the target maneuvering range. Under this guidance scheme, a preprogrammed covering strategy and an adaptive covering strategy are designed for the missile teams without and with communication capability respectively. The former attempts to specify different subsets of the target maneuvering range to different missiles as the expected reachable sets, while the latter aims to coordinate the expected reachable sets of different missiles dynamically according to the changing engagement situation. Considering the disadvantage of inferior maneuverability, the inherent limitations of the proposed guidance scheme are discussed. Numerical simulations with different target maneuvering modes demonstrate the prominent performance improvements of cooperative strategy over the traditional guidance laws.
Keywords: Cooperative interception; Coverage-based guidance law; Virtual aiming point